Can Surface Soil Moisture Information Identify Evapotranspiration Regime Transitions?. Issue 7 (5th April 2022) - Dong, Jianzhi; Akbar, Ruzbeh; Short Gianotti, Daniel J.; Feldman, Andrew F.; Crow, Wade T.; Entekhabi, Dara
Abstract: The transition of evapotranspiration between energy‐ and water‐limitation regimes also denotes a nonlinear change in surface water and energy coupling strength. The regime transitions are primarily dominated by available moisture in the soil, although other micro‐meteorological factors also play a role. Remotely sensed soil moisture is frequently used for detecting evapotranspiration regime transitions during inter storm dry downs. However, its sampling depth does not include the entire soil profile, over which water uptake is dominated by plant root distribution. We use flux tower, surface ( θ s ; observations at 5 cm), and vertically integrated in situ soil moisture ( θ v ${θ }_{v}$ ; 0–50 cm) observations to address the question: Can surface soil moisture robustly identify evapotranspiration regime transitions? Results demonstrate that θ s and θ v are hydraulically linked and have synchronized evapotranspiration regime transitions. As such, θ s and θ v capture comparable statistics of evapotranspiration regime prevalence, which supports the utility of remote‐sensing θ s for large‐scale land‐atmosphere exchange analysis. Plain Language Summary: During dry down periods between storms, soil moisture availability can be a limiting factor for evapotranspiration (water‐limited regime). In contrast, evapotranspiration is insensitive to soil moisture for adequately wet conditions, and is primarily determined by atmospheric evaporative demand (energy‐limited regime). During interstorm drydowns, the landscape changes from one regime to another. The timing of evapotranspiration regime change signifies a change in the coupling of landscape water and energy balances. Soil moisture based on microwave remote sensing has been frequently used for analyzing global‐scale evapotranspiration regime transitions. However, microwave signals are mainly sensitive to surface soil moisture ( θ s ), which is not directly a sampling of root water uptake from the deeper soil profile. Therefore, the applicability of remotely sensed θ s information for evapotranspiration regime identification is uncertain. In this study, we use flux tower, surface ( θ s, observations at 5 cm) and vertically integrated ( θ v, 0–50 cm) in situ observations to examine the reliability of θ s for evapotranspiration regime identification. Results demonstrate that θ s and θ v are equivalently skillful for identifying evapotranspiration regime changes and the time a landscape spends in the water‐limited regime. Therefore, remotely sensed θ s can be used to robustly analyze evapotranspiration regime changes and the associated large‐scale land‐atmosphere exchanges. Key Points: Observation‐based analysis shows that surface and root zone soil moisture are consistent in evapotranspiration regime identification During interstorm drydowns, surface soil moisture availability signifies the transition from energy‐ to water‐limited regime We demonstrate the general reliability of earth‐orbit retrieved surface soil moisture for large‐scale land‐atmosphere interaction studies